Is there a difference between intrapreneurs and early-stage entrepreneurs in Romania? - Annamária BENYOVSZKI; Ágnes NAGY; Tünde Petra PETRU (Theoretical and Applied Economics, 2013)

(untitled)
The aim of this paper is to study the differences between being an intrapreneur and an early-stage entrepreneur in Romania. We first present an international comparison of intrapreneurial and early-stage entrepreneurial activity rate, followed by the individual level analysis of these new venture creators using Global Entrepreneurship Monitor (GEM) database of Romania from 2012.